High magnetic field phase diagram and failure of the magnetic Grüneisen scaling in LiFePO4$ - Werner, Johannes; Sauerland, Sven; Koo, Changhyun; Neef, Christoph; Pollithy, Anna; Klingeler, Rüdiger (Physical review, 2019)
We report the magnetic phase diagram of single-crystalline LiFePO4 in magnetic fields up to 58 T and present a detailed study of magnetoelastic coupling by means of high-resolution capacitance dilatometry. Large anomalies at TN in the thermal-expansion coefficient α imply pronounced magnetoelastic coupling. Quantitative analysis yields the magnetic Grüneisen parameter γmag=6.7(5)×10−7 mol/J. The positive hydrostatic pressure dependence dTN/dp=1.46(11) K/GPa is dominated by uniaxial effects along the a axis. Failure of Grüneisen scaling below ≈40K, i.e., below the peak temperature in the magnetoelectric coupling coefficient [7], implies several competing degrees of freedom. A broad and strongly magnetic field dependent anomaly in α in this temperature regime highlights the relevance of structure changes. Upon application of the magnetic field B||b axis, a pronounced jump in the magnetization implies spin reorientation at BSF=32T as well as a precursing phase at 29 T and T=1.5K. In a two-sublattice mean-field model, the saturation field Bsat,b=64(2)T enables assessing the effective antiferromagnetic exchange interaction Jaf=2.68(5)meV as well as anisotropies Db=−0.53(4)meV and Dc=0.44(8)meV.
Im Titel ist die Zahl "4" tiefgestellt
Gesehen am 06.08.2019